Bread Sales Forecasting on Surya Bakery During Covid 19 Pandemic in Kota Bengkulu - Bimo Abrianto; Yun Fitriano; Tito Irwanto (Penerbit Jurnal Indonesia, 2021)
This study aims to determine how to forecast the amount of production of bread, donuts, cake, brownies and traditional cakes at Surya Baker in Bengkulu City with the time series method and the exponential smoothing method. This type of research uses quantitative research. with data collection techniques, namely interviews and documentation. The results show that forecasting the production of bread, donuts, cakes, brownies using the time series method with the trend projection approach obtained the equation y = a + bx = 9,394 + 577,615x with predicted production levels to decrease by 240,935 units per year with a percentage of 20% per year. years, while for the traditional type of cake and from the analysis it is known that the trend projection equation is obtained y = a + bx = 90,229 + 289,307x with the production rate predicted to increase by 1,146,959 packs with a percentage of 11% per year. Furthermore, with the calculation of forecasting demand for bread, donuts, cakes, brownies with the exponential smoothing method = 0.1, 0.5 and 0.9 amounting to 46,800 units, while the forecast for consumer demand for traditional cakes a = 0.1, 0.5 and 0.9 for 24,000 packs. From the equation line, as already analyzed the production forecasts for the months January 2021 to December 2021.